Parenting practices, self-control and adolescents rebellion from single and intact family - Lee, Wendy Wen Ni; Wong, Yoong Xin; Yee, Kyte Wie (2019)
Parenting practices are important in child development whereas inappropriate parenting practices may increase the chances on child rebellion. The aim of this study was to examine the relationship of parenting practices, self-control and rebellious behaviour among Malaysian adolescents and the moderating effect of family structure in those relationships. Purposive sampling was used to collect the data. In this research, 398 secondary students from both single and intact family were recruited. The results showed that there were significant relationships among parenting practices, self-control and adolescents rebellion. However, there were no moderating effect of family structure in relation of parenting practices, self-control and rebellion. Future research is recommended to use different variables as the moderator to obtain a more comprehensive research finding.